ANALISIS PELAYANAN INTERVENSI GIZI SPESIFIK INTEGRATIF STUNTING DI WILAYAH KERJA PUSKESMAS KECAMATAN PADEMANGAN JAKARTA UTARA - Octoviana Carolina (Yayasan Pendidikan Medika Indonesia, 2021)
The 2016 Global Nutrition Report noted that the prevalence of stunting in Indonesia was ranked 108 out of 132 countries. In a previous report, Indonesia was listed as one of 17 countries that experienced a double burden of nutrition, both excess and malnutrition. The stunting prevalence of DKI Jakarta Province from 27.5% (in 2013) to 17.7% (in 2018), the City of Administration area North Jakarta 0.59% (in 2018) and 0.5% (in 2019) to 3.35% (in 2020), and the District of Pademangan 0.7% (in 2018) and 0.4% (in 2019) to 6.42% (in 2020). This study aims to analyze the specific stunting integrative nutrition intervention service in the working area of ​​the Puskesmas Pademangan sub-district, North Jakarta. This qualitative research with rapid assessment procedure design uses primary data from in-depth interviews and FGDs and secondary data from document review. The results showed that planning and budgeting was not optimal, cross-sectoral cooperation and division of authority in government ranks which could be a potential obstacle to the acceleration of stunting prevention in the Pademangan sub-district, especially in the quality of stunting integrative specific nutrition intervention services carried out at the Pademangan District Health Center. In the input component, planning and budgeting as well as cross-sectoral cooperation and division of authority have not been carried out with direct implementation related to stunting integration. In the process component, namely services that are carried out on priority targets, they have been carried out but in terms of quality, namely knowledge about balanced nutrition and healthy living habits, it is still not implemented, especially by breastfeeding mothers and young women. In the output component, the quality of service, especially for mothers who provide exclusive breastfeeding and young women who receive blood-added tablets, has not yet been achieved. The role of cross-sectoral involvement and education from health workers to encourage mothers to provide exclusive breastfeeding and young women to regularly consume blood-added tablets need to be improved and fully supported. Keywords: